Analysis of Customer Satisfaction Using the SERVQUAL Method and Structural Equation Modeling (SEM) in Parking Services at Tanah Abang Wholesale Center Block A - Sudewo; Heri Muryanto (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
Parking services are one of the important factors influencing customer satisfaction in modern shopping centers. The high level of commercial activity at Tanah Abang Wholesale Center Block especially in areas with high trading activity such as Tanah Abang Wholesale Center (PGTA) Block A. Problems encountered include vehicle queues during peak hours, limited supporting facilities, and variations in the quality of officer service that have the potential to reduce customer satisfaction. This study aims to analyze the effect of service quality on customer satisfaction using the Service Quality (SERVQUAL) and Partial Least Squares-Structural Equation Modeling (PLS-SEM) methods. The study used a quantitative approach with a purposive sampling technique on 100 respondents who use parking services. Data were analyzed using SmartPLS software through outer model testing, inner model testing, and bootstrapping. The results showed that the dimensions of Assurance and Empathy had a positive and significant effect on customer satisfaction, while the dimensions of Tangibles, Reliability, and Responsiveness did not have a significant effect. These findings indicate that a sense of security, trust, and officer attention are the main factors that determine customer satisfaction compared to aspects of physical facilities and speed of service. This study concludes that improving officer competency, communication quality, and customer-oriented service are key strategies for improving parking service quality at PGTA Block A.